Counting on parents or others? : The role of social support for fertility intentions in Finland - Artamonova, Alyona; Sorsa, Tiia; Berg, Venla; Hägglund, Anna Erika; Rotkirch, Anna (Väestöliitto, 2025)
This study explores the associations between receiving social support from network members other than individuals’ parents and fertility intentions in Finland. It additionally examines whether support from others can compensate for the lack of parental support or complement their support. Using logistic regression models applied to Generations and Gender Survey (GGS) data on individuals aged 18–45 years enriched with administrative registers, we found that Finns who received instrumental support from others were more likely to intend to have a child. Support from others did not compensate for, nor complement, a lack of parental support or parental geographic remoteness. However, among men with at least one parent deceased or unknown, those receiving emotional support from others were more likely to intend to have a child within three years (and as likely as individuals with both parents alive) than those not receiving this support, suggesting a compensatory mechanism.